Geomorphological and vegetation interaction and its relationship to slope stability on the Niagara Escarpment, Bruce Peninsula, Ontario - Moss, Michael; Nickling, William (Géographie physique et Quaternaire, 1980)
The stability of the face of the Niagara Escarpment is a critical issue in the possible development of this important natural resource. In an attempt to provide background data for future resource management strategies a pilot study was initiated in the Hope and Barrow Bay section of the Bruce Peninsula. Results indicate that most of the initial erosion and steepening of the slopes resulted from the movement of glacial ice over the upper Escarpment. These steep slopes were maintained by low water stages of Lake Algonquin which resulted in the concentration of erosion in the relatively weak Fossil Hill Formation. At present instability is localized to certain parts of the Escarpment and appears to be both spatially random and sporadic, but is generally associated with certain conditions. Instability is usually found where outcrops of more resistant beds are being presently undercut by the weathering and mass wasting of weaker shale and heavily jointed dolomite beds. This activity is recognizable by lack of vegetation or by the dominance of Thuja occidentalis.